1972
DOI: 10.1128/iai.6.3.422-424.1972
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Streptococcus mutans Strains Based on Their Mannitol-1-Phosphate Dehydrogenases: Criterion for Rapid Classification

Abstract: Hexitol phosphate dehydrogenases were inducible in all strains of Streptococcus mutans studied, and these organisms could be placed into one of four groups according to the electrophoretic mobility of their mannitol-l-phosphate dehydrogenases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…S. mutans strains NCTC 10449, FAl, SL1, HS6, and AHT were generously provided by Albert T. Brown and Alan L. Coykendall. These strains of S. mutans are representative of each of the four genetic groups based on guanosine-cytosine ratios and deoxyribonucleic acid hydridization (9), kinetic activity of lactic dehydrogenase (5), and electrophoretic patterns of hexitol phosphate dehydrogenases (4), aldolases (25), enzymes of extracellular polysaccharide synthesis (7,31), and invertases (38). These characteristics all correlate well with the serological groups described by Bratthall (1).…”
Section: Methodssupporting
confidence: 67%
“…S. mutans strains NCTC 10449, FAl, SL1, HS6, and AHT were generously provided by Albert T. Brown and Alan L. Coykendall. These strains of S. mutans are representative of each of the four genetic groups based on guanosine-cytosine ratios and deoxyribonucleic acid hydridization (9), kinetic activity of lactic dehydrogenase (5), and electrophoretic patterns of hexitol phosphate dehydrogenases (4), aldolases (25), enzymes of extracellular polysaccharide synthesis (7,31), and invertases (38). These characteristics all correlate well with the serological groups described by Bratthall (1).…”
Section: Methodssupporting
confidence: 67%
“…Lesions of this type were completely absent in the gnotobiotic rats infected with the mutants but were present in WT-infected gnotobiotes. In conventionalized rats, their presence paralleled that of plaque-associated lesions on the smooth 6. Average number of carious enamel areas of uninfected gnotobiotic rats or those infected by strain 6715-13 WT or mutants.…”
Section: Figmentioning
confidence: 88%
“…Previously, Coykendall et al (6-10) had found by DNA/DNA homologies and guanineplus-cytosine content analyses that he could distinguish only four groups of S. mutans and that he could not distinguish between Bratthall serotypes c and e. Based on DNA buoyant densities (15), enzymological evidence (2,3,5,7), and cell wall analyses (21), others have reached similar conclusions. The present data provide biochemical evidence consistent with these groupings and additionally supply data consistent with the antigenic distinction between c and e (1, 28) and with the biochemical differences between c and e reported by others (5,7,29,35).…”
Section: Omz-176mentioning
confidence: 89%